2003
DOI: 10.1159/000073451
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Anxiety Disorders: A Comparison of Obsessive-Compulsive Disorder, Social Anxiety Disorder, and Panic Disorder

Abstract: Background: There is growing recognition that the anxiety disorders are disabling disorders associated with substantial morbidity and impaired quality of life (QOL). Nevertheless, there have been few studies comparing QOL across these conditions. Sampling and Methods: 337 outpatients with obsessive-compulsive disorder (OCD; n = 220), panic disorder (PD; n = 53), or social anxiety disorder (SAD; n = 64) were compared using a number of assessment scales to compare objective and subjective impairment in QOL. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(139 citation statements)
references
References 41 publications
10
123
0
5
Order By: Relevance
“…It has an early onset (80% of cases occur before age 18 years) (Otto et al, 2001), and often precedes other anxiety, mood, and substance abuse/dependence disorders (Lampe et al, 2003;Randall et al, 2001). SAD is associated with a significant functional impairment and distress in work and social domains and usually persists unless treated (Schneier et al, 1994;Lochner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has an early onset (80% of cases occur before age 18 years) (Otto et al, 2001), and often precedes other anxiety, mood, and substance abuse/dependence disorders (Lampe et al, 2003;Randall et al, 2001). SAD is associated with a significant functional impairment and distress in work and social domains and usually persists unless treated (Schneier et al, 1994;Lochner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies report that the decrease in productivity and quality of life of severely ill and/or treatment-resistant anxiety patients was comparable to those of schizophrenics. 10,11 Anxiety Disorders Association of America estimates the costs to be over 42 billion dollars per year comparable to those of stroke and cardiovascular disorders. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The study of Lochner and colleagues revealed that SAD affects quality of life, especially in matters which are related to leisure activities and social life [30]. Furthermore, the study of Barrera and Norton (2009) has also found that the quality of life of patients with SAD is poorer, same with those who are suffering from general anxiety disorder and panic disorder [31].…”
Section: Discussionmentioning
confidence: 99%